Drug resistant tuberculosis: biology, epidemiology and control - Dye, Christopher (Henry Stewart Talks, 2009)
Natural history and epidemiology of TB, Discovery of antibiotics, Drug combinations as used in TB control programmes worldwide, How drug resistance arises, Geographical distribution of drug-resistant TB, TB drug resistance and HIV/AIDS, Reversing the spread of drug-resistant TB
Reviewed at 2015/08/06